Comparative efficacy of solifenacin and tamsulosin in alleviating stent-related symptoms: A systematic review and meta-analysis - Harahap, Dianita H.; Adhyatma, Kharisma P.; Elbert, Elbert; Khosasi, Felix; Warli, Muhammad H. (Narra J, 2025)
Ureteral stents, commonly used in urology, can cause side effects affecting patient quality of life. However, studies on managing lower urinary tract symptoms showed inconsistencies due to the use of various alpha-blockers and antimuscarinic drugs. The aim of this study was to evaluate the effectiveness of combining tamsulosin and solifenacin therapy compared to tamsulosin and solifenacin monotherapy for treating stent-related symptoms. Randomized controlled trials assessing tamsulosin, solifenacin, or their combination for stent-related symptoms treatment were identified through a comprehensive search of four databases (PubMed, Scopus, Web of Science, and Cochrane) from January 2018 to December 2023. Ureteral stent symptom questionnaire (USSQ), international prostate symptom score (IPSS), visual analog scale (VAS), and quality of life (QoL) were pooled for meta-analysis. Eleven studies with a total of 1,627 patients were included in the quantitative analysis. Solifenacin significantly improved urinary symptoms (MD: 15.31; 95%CI: 0.36–30.26; p=0.040) and reduced the IPSS (MD: -2.52; 95%CI: -3.68–-1.36; p<0.00001) compared to the control group. Tamsulosin reduced urinary symptoms on the USSQ (MD: 14.27; 95%CI: 8.68–19.86; p<0.00001), general health problems (MD: 4.53; 95%CI: 2.13–6.94; p=0.0002), and IPSS (MD: -0.95; 95%CI: -1.86–-0.03; p<0.00001) compared to the control group. Solifenacin demonstrated a more significant reduction in the overall IPSS compared to tamsulosin (MD: -1.57; 95%CI: -2.85–-0.29; p=0.020). The combination of solifenacin and tamsulosin resulted in a significantly superior reduction in IPSS compared to solifenacin monotherapies (MD: -2.30; 95%CI: -3.23–-1.37; p<0.00001) and tamsulosin monotherapy (MD -3.17; 95%CI: -5.07–-1.27; p=0.00001). No significant differences were found between tamsulosin and solifenacin in terms of QoL (MD: 0.12; 95%CI: -0.01–0.26; p=0.070) and VAS (MD: 0.25; 95%CI: -0.95–1.44; p=0.690). In conclusion, solifenacin was more effective than tamsulosin in reducing stent-related symptoms, and the combination of tamsulosin and solifenacin was superior to either monotherapy in alleviating stent-related symptoms.